Contribution of Ladder Drill and Dryland Circuit Training to 50-meter Freestyle Swimming Speed in 13-to-14 Male Swimmers Aquatic Swimming Club - James Dionisius Simbolon; Novita Novita (Journal of Indonesian Active in Sports, 2024)
The objective of this study was to assess the impact of ladder drill and dryland circuit exercises on the pace of 50-meter freestyle swimming in male swimmers aged 13-14 years at the Aquatic Swimming Club in Medan. The researchers employed an experimental approach utilising a pre-experimental design consisting of a single group with pretest and posttest measurements. The sample comprised 8 adolescent male swimmers, aged 13-14 years, who were actively involved in the club. They were recruited via purposive sampling. The study was carried out for a duration of 6 weeks, consisting of 18 training sessions, conducted 3 times a week. Measurements were obtained using 40-meter sprint tests, medicine ball throw tests, and 50-meter freestyle swimming speed tests conducted both before and after the training treatments. The data underwent analysis through normality tests, homogeneity tests, correlation tests, and regression tests. The findings demonstrated that ladder drill training made a noteworthy contribution of 59.29% to enhancing 50-meter freestyle swimming speed. Similarly, dryland circuit training had a substantial impact, accounting for 77.44% of the improvement. Furthermore, when both training methods were combined, they together contributed 62% to the enhancement of swimming speed. The study found that both ladder drill and dryland circuit training have a substantial impact on improving the 50-meter freestyle swimming speed of male swimmers aged 13-14 at the Aquatic Swimming Club in Medan. Additionally, the dryland circuit training was found to have a greater effect than the ladder drill.